A comparison of two complete feed blocks based on sorghum stover of two different cultivars on weight gain in sheep and economy of feeding - Samireddypalle, A.; Khan, A.A.; Ravi, D.; Blümmel, Michael (2010)
The effect of different sorghum stover fodder quality in densified total mixed ration (DTMR) feed blocks was investigated. An experimental feed block with a low cost stover was compared with a commercial feed block produced by Miracle Feeds and Fodder Pvt. Ltd. that consisted of a premium sorghum stover (about 50%) and concentrate in equal proportions. Concentrate component consisted of bran and husks/hulls (18%), oilcakes (18%), molasses (8%) with the rest contributed by maize grain, urea, minerals and vitamins. In the experimental DTMR feed block the premium stover was replaced by low cost stover and rest of the composition was same. The two blocks were fed ad libitum to growing sheep measuring intake, digestibility and weight gain. No difference was observed in digestibility between the groups fed the commercial and the experimental block. Intake in the group fed the commercial block was 37 g/kg LW compared to 32.8 g/kg LW in the experimental block group (P=0.07). Daily live weight gain in the former group was twice that of the latter (90 vs. 45g; P=0.04). However, both feeding regimes were uneconomical, with the experimental feeding regime even resulting in monetary loss.